2015
DOI: 10.1007/s13277-015-3195-7
|View full text |Cite
|
Sign up to set email alerts
|

SUZ12 promotes gastric cancer cell proliferation and metastasis by regulating KLF2 and E-cadherin

Abstract: SUZ12 is a core component of the polycomb repressive complex 2 (PRC2), which could silence gene transcription by generating trimethylation on lysine 27 residue of histone H3 (H3K27Me3). Meanwhile, SUZ12 has been found to be overexpressed in multiple cancers; however, the clinical significance and molecular mechanisms of SUZ12 controlling gastric cancer cell proliferation and metastasis are unclear. In this study, we found that SUZ12 expression was significantly increased in 64 gastric tumor tissues compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 31 publications
5
41
0
1
Order By: Relevance
“…There is evidence showed that its expression is diminished in multiple cancers and possesses tumor-suppressor features for its inhibitory effects on cell proliferation [31, 32], and our previous study showed that SUZ12 could repress its expression in gastric cancer cells [33]. In this study, we also found that KLF2 can function as tumor suppressor and its' expression could be suppressed by ZFAS1 through recruiting EZH2 and LSD1 to its promoter region in gastric cancer cells.…”
Section: Discussionsupporting
confidence: 61%
“…There is evidence showed that its expression is diminished in multiple cancers and possesses tumor-suppressor features for its inhibitory effects on cell proliferation [31, 32], and our previous study showed that SUZ12 could repress its expression in gastric cancer cells [33]. In this study, we also found that KLF2 can function as tumor suppressor and its' expression could be suppressed by ZFAS1 through recruiting EZH2 and LSD1 to its promoter region in gastric cancer cells.…”
Section: Discussionsupporting
confidence: 61%
“…Inhibition of PI M2 is a promising avenue for the treatment of multiple myeloma 65 . Su(z)12 is part of the ubiquitous polycomb repressive complex 2 (PRC2) and is overexpressed in numerous cancers, including gastric cancer where Su(z)12 levels were associated with increased metastasis and unfavorable survival prognosis 67 . The ETS family of transcription factors has demonstrated significant involvement in all stages of tumorigenesis 68 , while FoxA1 is known as ‘pioneer transcription factor in organogenesis and cancer progression’ 69 .…”
Section: Resultsmentioning
confidence: 99%
“…SNAI1-PRC2 interaction can also be bridged by Ajuba LIM, PRMT5 or a mediator protein MEP50 [135,136]. In gastric cancer cells, PRC2 is also recruited through SUZ12 and catalyzes H3K27me3 on KLF2 and E-cadherin promoters [137]. Intriguingly, an H3K4me3 to H3K27me3 switch was observed on 102 EMT marker gene promoters including E-cadherin in a TWIST1-induced EMT cell model.…”
Section: Permissive Histone Modifications In Emtmentioning
confidence: 99%